Gamification of Immersive Meditation Practice in Virtual Reality - Matthew John Moroz; Bianca Calagiu (Journal of Games, Game Art, and Gamification, 2018)
Benefits arising from meditation practice gamification are not overtly obvious. Desires to achieve and progress to higher levels, which are common to gaming, seem diametrically opposed to the ethos underlying traditional meditation practice. We propose, however, that a motivation to gain greater wellbeing and enlightenment via mindfulness meditation practice shares more with the motivation to progress through a game than is initially apparent. We begin by explaining how gamification techniques may be employed in meditation practice with a focus on mitigating the five hindrances to successful practice as described in the Theravada tradition. We then highlight the utility of employing virtual reality as a medium for such simulations. We discuss the potential for beneficial therapeutic applications in patients with mental health disorders and prison populations. We conclude by summarising our position and urging increased attention in this increasingly relevant area of research.